Study of Capacitive and Electrical Conductivity Characteristics of the System «Nanostructured Electrodes - Dielectric Liquid» - S.G. Emelyanov; A.E. Kuz'ko; A.V. Kuz'ko; P.A. Ryapolov (Журнал нано- та електронної фізики)
The results of research of capacitive and conductive characteristics of the system "the nanostructured metal electrodes – dielectric liquid" are given. It is shown the difference of states near the electrodes of electric double layers on the surfaces of copper and tungsten electrodes.